Antecendents and Consequences of Trancedental Knowledge Sharing to Improve Work Performance - M. Rahmawan Arifin (Shirkah: Journal of Economics and Business, 2020)
This study was undertaken in an attempt to build a theoretical model through an in-depth study on the effect of transcendental knowledge sharing on the budget implementation performance as well as novelty in answering the gap between affective commitments on employee performance, especially the finance staff at the State Islamic Religious College (PTKIN). IAIN Surakarta has encountered rapid academics and financial governance development in the last 4 years. As a non-BLU (non-public service agency) college with the largest number of students and PNBP (non-tax state revenues) in Indonesia, IAIN Surakarta requires a strategy in improving employee performance, especially the finance staff. This study uses a non-probability purposive sampling. The questionnaire was distributed to 230 respondents consisting of leaders, structural officials, finance staff, lecturers receiving research assistance, and administrators of the student activity unit (UKM). By using the Structural Equation Model (SEM) method, data and hypotheses are analyzed using AMOS 21.0 software. The results of the study highlighted that transcendental knowledge sharing has a significant effect on the performance of finance staff. Transformational leadership, Organizational Citizenship Behavior (OCB) and affective commitments with transcendental knowledge sharing mediation significantly affect the budget implementation performance. The implication of the research is to strengthen the financial policies at IAIN Surakarta and professional governance to improve the budget implementation performance.